E183K Mutation in Chalcone Synthase C2 Causes Protein Aggregation and Maize Colorless - Dong, Haixiao; Li, He; Xue, Yingjie; Su, Shengzhong; Li, Shipeng; Shan, Xiaohui; Liu, Hongkui; Jiang, Nan; Wu, Xuyang; Zhang, Zhiwu; Yuan, Yaping (Frontiers in Plant Science, 2021)
Flavonoids give plants their rich colors and play roles in a number of physiological processes. In this study, we identified a novel colorless maize mutant showing reduced pigmentation throughout the whole life cycle by EMS mutagenesis. E183K mutation in chalcone synthase C2 (ZmC2) was mapped using MutMap strategy as the causal for colorless, which was further validated by transformation in Arabidopsis. We evaluated transcriptomic and metabolic changes in maize first sheaths caused by the mutation. The downstream biosynthesis was blocked while very few genes changed their expression pattern. ZmC2-E183 site is highly conserved in chalcone synthase among plantae kingdom and within species' different varieties. Through prokaryotic expression, transient expression in maize leaf protoplasts and stable expression in Arabidopsis, we observed that E183K and other mutations on E183 could cause almost complete protein aggregation of chalcone synthase. Our findings will benefit the characterization of flavonoid biosynthesis and contribute to the body of knowledge on protein aggregation in plants.